A Cloud Architecture for Networked and Autonomous Vehicles⁎This research is accomplished within the project "UNICARagil" (FKZ EM2ADIS002). We acknowledge the financial support for the project by the Federal Ministry of Education and Research of Germany (BMBF). Issue 2 (2021) - Mokhtarian, Armin; Kampmann, Alexandru; Lueer, Maximilian; Kowalewski, Stefan; Alrifaee, Bassam
Abstract: This paper outlines a novel framework for a cloud-based computational model that supports the interconnection of autonomous vehicles, road-infrastructure and humans. Besides serving as a central entity to call autonomous vehicles like the private vehicle, taxi or bus, this architecture can be used to automate and manage vehicle delivery services. Examining these different application domains led to a service-oriented cloud architecture that distinguishes between two kinds of services. Domain dependent services for each of the vehicle types and core services which are imperative for all applications. Since several core services require realtime vehicle-to-cloud communication, we present and evaluate a suitable communication system. This cloud architecture is characterized by its modular design in order to enable adaptation to different system requirements. In fact, it has found its application in the UNICARagil project, where four types of networked and autonomous vehicles are developed.